Optimalisasi Pengendalian Persediaan Bahan Baku Mie Menggunakan Metode Min-Max Stock untuk Meminimumkan Biaya Persediaan pada PT Dapur Boga Lestari - Rahmadhani, Talitha Vania; Ernawati, Dira (Ekonomis: Journal of Economics and Business, 2024)
PT Dapur Boga Lestari is a company that produces noodles and is located in Sidoarjo, East Java Province. Flour and eggs are the primary ingredients in the noodles themselves. In meeting its requirements, the business frequently faces numerous obstacles. PT Dapur Boga Lestari lacks a distinct company-wide method for controlling these basic materials. Despite the fact that the company must control the inventory of raw materials for flour and eggs in order to prevent shortages and excesses of raw materials, which incur additional costs for the company, The results of the calculations indicate that the min-max stock method yields a lower total cost than the company method. In each period, the min-max stock method results in a 19% cost reduction for flour raw materials. In terms of egg primary materials, the company saved 29% from April 2023 to February 2024 and 25% from March 2024 to January 2025. This research provides information that assists businesses in identifying investments that will not benefit their production processes.